Fabrication of four-channel DFB laser array using nanoimprint technology for 1.3μm CWDM systems - 赵建宜 陈鑫 周宁 黄晓东 刘文 (Journal of semiconductors, 2014)
Four-channel monolithically integrated index-coupled distributed-feedback laser array has been fabricated using nanoimprint technology for 1.3μm CWDM system. Selective lasing wavelength with 20 nm wavelength space is obtained. The present results show that the nanoimprint technology is mature and reliable in the fabrication of DFB laser array.